Development of Student Worksheet based on STEM to Improve the Critical Thinking Skills - Hayatul Husna; Retno Dwi Suyanti; Anita Yus (RIRAI Publisher, 2023)
Based on the results of observations, it shows that the development of student worksheets is not optimal, especially in science learning with water cycle material which should be adapted to developments in the 21st century, as science learning is fun learning if it is created well. The 21st century requires students to have various skills, one of which is critical thinking skills. because students are required to be more responsive in analyzing, solving problems and solving problems in the learning process. The aim of this research is to develop and determine the feasibility of STEM-based student worksheets with water cycle material for fifth grade elementary school students. This research method is Research and Development (R&D), which is a research method used to develop or validate products used in education and learning. The results of the research show that the process of developing student worksheets to train critical thinking skills consists of three stages, namely preliminary study, product development, and test the product. The student worksheets were validated by three expert validators, namely design expert validation, material expert and language expert with respective scores of 84.37%, 94% and 91.42% with very feasible criteria. So, it can be concluded that this STEM-based student worksheets with water cycle material is suitable for use as a learning companion for students to improve students' critical thinking skills KEYWORDS